Long access to cocaine self‐administration dysregulates the glutamate synapse in the nucleus accumbens core of serotonin transporter knockout rats. (20th May 2021) - Caffino, Lucia; Mottarlini, Francesca; Targa, Giorgia; Verheij, Michel M. M.; Homberg, Judith; Fumagalli, Fabio
Abstract : Background and Purpose: It is well established that the nucleus accumbens and glutamate play a critical role in the motivation to take drugs of abuse. We have previously demonstrated that rats with ablation of the serotonin (5‐HT) transporter (SERT −/− rats) show increased cocaine intake reminiscent of compulsivity. Experimental Approach: By comparing SERT −/− to SERT +/+ rats, we set out to explore whether SERT deletion influences glutamate neurotransmission under control conditions as well as after short access (1 h/session) or long access (6 h/session) to cocaine self‐administration. Key Results: Rats were killed at 24 h after the final self‐administration session for ex vivo molecular analyses of the glutamate system (vesicular and glial transporters, post‐synaptic subunits of NMDA and AMPA receptors and their related scaffolding proteins). Such analyses were undertaken in the nucleus accumbens core. In cocaine‐naïve animals, SERT deletion evoked widespread abnormalities in markers of glutamatergic neurotransmission that, overall, indicate a reduction of glutamate signalling. These results suggest that 5‐HT is pivotal for the maintenance of accumbal glutamate homeostasis. We also found that SERT deletion altered glutamate homeostasis mainly after long access, but not short access, to cocaine. Conclusion and Implications: Our findings reveal that SERT deletion may sensitize the glutamatergic synapses of the nucleus accumbens core to the long access but not short access, intake of cocaine. LINKED ARTICLES: This article is part of a themed issue on New discoveries and perspectives in mental and pain disorders. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.17/issuetoc